The Association between Unhealthy Food Consumption and Impaired Glucose Metabolism among Adults with Overweight or Obesity: A Cross-Sectional Analysis of the Indonesian Population - Adriyan Pramono; Deny Y. Fitranti; K. Heri Nugroho; M. Ali Sobirin; Ahmad Syauqy (Hindawi Limited, 2023)
Background. It has been shown that dietary patterns are associated with glucose control. However, the association between the types of food consumed and blood glucose in overweight or obese individuals is still unclear. The present study aimed to determine the association between unhealthy food consumption and impaired glucose metabolism in adults with overweight or obesity. Methods. The analysis presented in this study was based on the data from a population-based, cross-sectional, nationally representative survey (Indonesian Basic Health Research 2018/RISKESDAS 2018). The body mass index (BMI) was calculated as weight (kg)/height squared (m2) and was determined based on the World Health Organization (WHO) criteria for the Asian population. A validated questionnaire and food card were used to assess the diet. Fasting plasma glucose and 2-hpost-prandial glucose were employed to determine blood glucose markers. Results. In total, 8752 adults with overweight or obesity were included in this analysis. We found that consumption of sweet, grilled, and processed foods was associated with impaired fasting plasma glucose (IFG) before and after adjustment (p<0.05). Consumption of high-fat foods was also associated with impaired glucose tolerance (IGT) for all models tested (p<0.05). Furthermore, all models showed a link between processed food consumption and combined glucose intolerance (CGI) (p≤0.001). Conclusions. Differential food group consumption was associated with IFG, IGT, and CGI in Indonesian adults who were overweight or obese.